2014
DOI: 10.2174/0929866521666140526152426
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analyses of Soybean Root Tips During Germination

Abstract: Plant root systems form complex networks with the surrounding soil environment and are controlled by both internal and external factors. To better understand the function of root tips of soybean during germination, three proteomic techniques were used to analyze the protein profiles of root tip cells. Proteins were extracted from the root tips of 4-dayold soybean seedlings and analyzed using two-dimensional (2D) gel electrophoresis-based proteomics, SDS-gel based proteomics, and gel-free proteomics techniques.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…During flooding, the concentration of NADH and NAD + is increased and the ATP level decreased, which indicates impairment of the electron transport chain, while the amount of mitochondrial NADH gets increased. Flooding stress modulates the urea cycle and enhances the synthesis of PEP through oxaloacetate produced in the TCA cycle [114]. The intermediate or end product of the metabolic pathways play a vital role in several biochemical processes and phenotypic traits, including root traits [115].…”
Section: Abiotic Stress Tolerancementioning
confidence: 99%
“…During flooding, the concentration of NADH and NAD + is increased and the ATP level decreased, which indicates impairment of the electron transport chain, while the amount of mitochondrial NADH gets increased. Flooding stress modulates the urea cycle and enhances the synthesis of PEP through oxaloacetate produced in the TCA cycle [114]. The intermediate or end product of the metabolic pathways play a vital role in several biochemical processes and phenotypic traits, including root traits [115].…”
Section: Abiotic Stress Tolerancementioning
confidence: 99%
“…Even though soybean is a recalcitrant plant species, protein extraction protocols have been standardized to achieve optimized 2-DE results in terms of protein spot number and spot intensity. 181 Different tissue-specific proteomic studies have revealed that phenol and tricyclic antidepressant/acetonebased extraction protocols are most suitable for soybean protein extraction. The construction of detailed quantitative soybean proteome reference maps facilitates functional genomic studies and also provides an essential tool for the rapid identification of soybean mutants/transgenic lines.…”
Section: The Current Status Of Proteomics In Soybeanmentioning
confidence: 99%
“…Overall, the scenario of soybean proteomics has started to change since the completion of the soybean draft genome sequence. Even though soybean is a recalcitrant plant species, protein extraction protocols have been standardized to achieve optimized 2-DE results in terms of protein spot number and spot intensity . Different tissue-specific proteomic studies have revealed that phenol and tricyclic antidepressant/acetone-based extraction protocols are most suitable for soybean protein extraction.…”
Section: Agricultural Problems and The Current Status Of Crop Proteomicsmentioning
confidence: 99%